Green Without Draining: Ending the Paradox of Resource Waste in the Implementation of the Green Madrasah Program in Indonesia - Korry Asri (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The Green Madrasah program in Indonesia is currently trapped in a paradox of maladaptation, where environmental conservation efforts actually trigger the depletion of water and financial resources due to assessment standards trapped in administrative formalities. This policy research aims to formulate a strategy for transforming green madrasah governance into a more sustainable one by eliminating greenwashing practices and bureaucratic burdens. The policy methodology used is a Descriptive-Qualitative Analysis with a Targeted Policy Study approach, which integrates a theoretical literature review—including Maladaptation and Institutionalism Theory—with secondary data analysis from the Indonesian Environmental Statistics and related regulations. The analysis is conducted by evaluating the gap between central agency assessment instruments and the reality of managerial capacity at the madrasah level. The analysis results indicate that a rigid orientation toward physical evidence has distorted the goals of ecological education into mere paperwork. As a solution, this article recommends a redesign of the assessment instrument through a Directorate General of Islamic Education Decree that shifts the focus from physical validation to the evaluation of substantive behavior change, supported by digitalized reporting, flexible BOS funds, and low-maintenance infrastructure standards. Implementing these recommendations is projected to restore madrasah financial stability, optimize water conservation, and restore their role as centers of authentic ecological character education. Through this paradigm shift, the concept of